Structural change through innovation: New elements in funding guidelines - Florian Wittmann; Esther Schnabl; Andrea Zenker (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2025)
Policies aimed at supporting economically lagging regions have changed considerably in the past decades. This includes an increased link between innovation and regional policy, as well as more recently transformative policy. The WIR! Programme, funded by the Ministry of Research and Education in Germany, introduces several policy innovations in this regard, such as an explicit link between innovation and structural change, the emphasis on involving new (societal) actors, and a broad understanding of innovation. Although such innovations have the potential to provide a fresh start for policy-making, it remains an open question how applicants and programme administrations cope with a changing funding environment. This paper investigates - by examining applicant structure, project outlines, and funding decisions - how these new requirements are taken into account. While evidence in favour of a partial reorientation is found, the analysis reveals a strong continuity of established patterns and priorities, with many project outlines focusing mostly on technological innovation and relatively narrow stakeholder involvement. These findings suggest that while initiatives like WIR! may provide new impulses, it may take longer for applicants and programme management to adjust to changing policy paradigms.
Keywords: 330; Regionalpolitik; Strukturschwache Region; Innovation; Strukturwandel; Wirkungsanalyse; Deutschland